2014
DOI: 10.1016/j.apcata.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional acid–base ionic liquid for the one-pot synthesis of fine chemicals: Thioethers, 2H-chromenes and 2H-quinoline derivatives

Abstract: More specifically, the catalyst can be successfully applied for different carbon-carbon (C-C) and carbon-heteroatom (C-N, C-O, C-S) bond forming reactions integrated in a cascade sequence. The activity of the organocatalyst has been compared with that of structurally related monofunctional and bifunctional catalysts.The most attractive features of this procedure are the high atom economy, the use of inexpensive starting materials as well as the use of an environmentally friendly catalyst that can be easily rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Very recently, Sabater and co-workers reported another organocatalytic approach to 2 H -chromenes involving the coupling of salicylaldehyde with different electron-deficient alkenes in the presence of an ionic liquid catalyst 343 (Scheme ). Although these particular reactions are not enantioselective, they are nonetheless included here in section for completeness.…”
Section: Enantioselective Organocatalytic 2h-chromene Synthesismentioning
confidence: 99%
“…Very recently, Sabater and co-workers reported another organocatalytic approach to 2 H -chromenes involving the coupling of salicylaldehyde with different electron-deficient alkenes in the presence of an ionic liquid catalyst 343 (Scheme ). Although these particular reactions are not enantioselective, they are nonetheless included here in section for completeness.…”
Section: Enantioselective Organocatalytic 2h-chromene Synthesismentioning
confidence: 99%
“…In the past several years, considerable effort has been made to build chiral chroman derivatives with multichiral centers via asymmetric domino reactions 3 catalyzed by aminocatalysts, 4 thiourea organocatalysts 5 squaramide organocatalysts, 6 and other organocatalysts. 7 Among these approaches, the addition to nitroolefins is a simple but highly efficient route to obtain chiral chromans containing nitro-group, and the nitro group can often lead to changes in chemical and physical properties. 4 d – h ,4 j ,5 b – d In 2013, Zhu et al reported the organocatalytic oxa-Michael-Michael cascade strategy for the construction of spiro [chroman/tetrahydroquinoline-3,3′-oxindole] scaffolds from 2-hydroxynitrostyrenes and N-Boc-protected methyleneindolinones using a squaramide-cinchona bifunctional catalyst.…”
mentioning
confidence: 99%
“…Based on the above experimental findings and relative cooperative catalysis reports, [19,23,39] a possible reaction pathway for the reaction of 1 a with 2 a over [SO 3 HPrMIm][OTf] is proposed as illustrated in Scheme 5. Initially, [SO 3 HPrMIm][OTf] activates 2 a by two hydrogen bonds via transient state TS1, meanwhile it catalyzes 1 a dehydration to form dibenzyl ether intermediate 5 a stabilized by the IL.…”
Section: Resultsmentioning
confidence: 99%